2004
DOI: 10.1099/vir.0.19530-0
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 1 infection of polarized epithelial cells requires microtubules and access to receptors present at cell–cell contact sites

Abstract: Mucosal epithelia are invaded from the apical surface during a primary infection by herpes simplex virus type 1 (HSV-1). HSV-1 progeny virus, synthesized from latently infected peripheral neurons that innervate such epithelia, reinfects the epithelia most likely from the basolateral surface. The epithelial cell lines MDCK and Caco-2 can be induced in vitro to differentiate into polarized cells with distinct apical and plasma membrane domains separated by tight junctions if they are cultured on porous membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 46 publications
3
38
0
Order By: Relevance
“…Previous studies have reported on HSV infection of epithelial cells by either the basolateral surface (25,38) or by both the apical and basolateral surfaces (16,17,25,39,46,47,55). HSV can apparently enter HaCaT keratinocytes from either the apical or the basolateral surfaces by endocytosis, although the basolateral domain seems to be preferred at low MOI ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported on HSV infection of epithelial cells by either the basolateral surface (25,38) or by both the apical and basolateral surfaces (16,17,25,39,46,47,55). HSV can apparently enter HaCaT keratinocytes from either the apical or the basolateral surfaces by endocytosis, although the basolateral domain seems to be preferred at low MOI ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6A). The preference of HSV for infecting exterior cells of Madin-Darby canine kidney cell islets has been noted previously (25,38). At high MOI, however, HSV entered (Fig.…”
Section: Lysosomotropic Agents Inhibit Hsv Infection Of Human Keratinmentioning
confidence: 95%
See 1 more Smart Citation
“…Accordingly, actin and microtubules are required for the efficient entry of herpes simplex type 1 and simian virus 40, respectively (Pelkmans et al, 2002;Marozin et al, 2004). It has been shown that disrupting the actin network can inhibit infection of HIV-1 and fusion with the host cell (Iyengar et al, 1998;Jernigan et al, 2000), presumably by disrupting the colocalization of CD4 and CXCR4 (Iyengar et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This process is aided by viral capsid protein VP26 and tegument protein U L 34. The capsids are propelled through the negative end of microtubules and released into nucleus through nuclear pore complexes (NPCs) [46][47][48][49][50].…”
Section: Viral Entrymentioning
confidence: 99%